Measles Virus Infection and Replication in Undifferentiated and Differentiated Human Neuronal Cells in Culture - McQuaid, S. (American Society for Microbiology, 1998)
Measles virus (MV) infection of the human central nervous system (CNS) typically involves widespread infection of neurons. However, little is known about how they become infected, how defective virus arises and accumulates, or how virus spreads among the cells of the CNS. In vitro studies of viral interactions with human neuronal cells may contribute to the resolution of such issues. In mixed cultures containing differentiated human neuronal (hNT2) cells and neuroepithelial cells, immunofluorescence studies show that the neurons, unlike both their NT2 progenitors and the neuroepithelial cells, are not initially susceptible to MV infection. This is possibly due to their lack of expression of CD46, a known cell surface receptor for MV. Later in the course of infection, however, both MV proteins and genomic RNA become detectable in their processes, where they contact infected, fully permissive neuroepithelial cells. Such a mechanism of virus transfer may be involved in the initiation and spread of persistent MV infection in diseases such as subacute sclerosing panencephalitis. Furthermore, mutated defective virus may readily accumulate and spread without the need, at any stage, for viral maturation and budding.